Rectoris longibarbus, a new styglophic labeonine species (Teleostei: Cyprinidae) from South China, with a note on the taxonomy of R. mutabilis (Lin 1933) - Zhu, Ding-Gui; Zhang, E; Lan, Jia-Hu (Zootaxa, 2012)
Rectoris longibargus, new species, is here described from the Zuo–Jiang of the Pearl River drainage at Jinxi County,Guangxi Province, China. It is distinct from all other congeners in the rostral barbel length and the structure of the gas-bladder. Rectoris longibarbus is further distinguished from R. posehensis by having a slightly papillated posteromedianpatch on the median plate of the lower lip, and from R. mutabilis, as here understood, by having a longitudinal black striperunning along the lateral line on the flank. Taxonomic problems with R. mutabilis are also addressed; it is regarded to bea senior synonym of R. luxiensis. The type locality of R. mutabilis is likely in the Yuan–Jiang (a tributary of the middleYangtze River drainage) in Guizhou Province. The species currently recognized as R. mutabilis is previously unnamed, and possibly represents an undescribed genus.